Performance of warm asphalt mixtures containing reclaimed asphalt pavement, an anti-stripping agent, and recycling agents: A study using a balanced mix design approach. (11th January 2023) - Yousefi, Afshar A.; Haghshenas, Hamzeh F.; Shane Underwood, Benjamin; Harvey, John; Blankenship, Phillip
Graphical abstract: Highlights: The performance of the mixtures is influenced by the type of recycling agents. WMA additive has a positive effect on performance of mixtures without RAP. At intermediate temperature, RAP lowers the flexibility index. RAP has a positive effect on rutting and moisture damage resistance of mixtures. Performance interaction diagram approach should be included in designing mixtures. Abstract: This research aims to use a balanced mix design (BMD) approach to investigate the effect of recycling agents (RAs) and an anti-stripping agent on the mechanical properties of warm-mix asphalt (WMA) containing different levels of reclaimed asphalt pavement (RAP). The BMD used three RAs (aromatic extract, triglycerides and fatty acids, and tall oil), an amidoamine WMA additive (PAWMA®), and an anti-stripping agent (Zycotherm®). The Dynamic Creep (DC), Indirect Tensile Strength (ITS), and Semi-Circular Bending (SCB) fracture tests were respectively used to evaluate the rutting, moisture susceptibility, and cracking resistance of mixtures. In addition, two-dimensional and three-dimensional (2-D and 3-D) performance interaction diagrams were developed as typical approaches for the BMD of asphalt mixtures. For mixtures with RAP, the results indicated that the aromatic extract and tall oil RAs decreased the moisture susceptibility, while triglycerides and fatty acids increased the moisture susceptibility. In addition, the RAs generally decreased the rutting resistance of mixtures while they increased the cracking resistance. This effect was more noticeable in the mixtures treated with triglycerides and fatty acids. The results also showed that introducing PAWMA® and Zycotherm® to the mixtures improved their resistance to moisture damage, cracking, and rutting.